Theatrical Writing. The Blind: A Symbolist Tragedy (2018)
In the present text, I present The blind by Maurice Maeterlink as a “Greek tragedy”. In dramatic terms, it presents the languor and existential faintness of men, the helplessness and orphanage in which he finds himself before an incomprehensible, depressive and dark design. Arguments are based on the importance that Nietzsche assigns to the choir, as an Apollonian role to make suffering explicit. Likewise, I propose that Maeterlinck does not hesitate to make a great chorus of this piece that proclaims the truth of the world, one of “the frightful and absurd of being”.